Keputusan Pembelian Minuman dan Ice Cream yang Dipengaruhi oleh Kualitas Produk dan Kualitas Pelayanan : (Studi Kasus Mahasiswa Konsumen Mixue Ice Cream & Tea di Politeknik LP3I Medan) - Maulidina Maulidina; Faizatul Izzati (Universitas 17 Agustus 1945, 2024)
This research discusses the influence of product quality and service quality on purchasing decisions for Mixue Ice Cream & Tea. The aim of this research is to determine the influence of product quality (X1) and service quality (X2) on purchasing decisions (Y). This research uses indicators from each variable. The indicators of Product Quality (X1) are color, appearance, portion, aroma, taste. Indicators of Service Quality (X2) are reliability, responsiveness, assurance, empathy, physical evidence. Indicators of Purchasing Decisions (Y) are product choice, brand choice, dealer choice, purchase time. This research uses quantitative methods with a population of 80 people and a sample of 80 people, while processing research data uses the SPSS version 26 program. Based on the research results, it can be seen that product quality variables and service quality variables partially have a significant effect on purchasing decision variables as proven in The results of the T test research with a calculated t value of 5.571 > t table 1.991 and a significant value of 0.000 < 0.05. And it is also known that the product quality variable and the service quality variable simultaneously have a significant effect on the purchasing decision variable from the F test with a significant value of 0.000 < 0.05 and a calculated F value of 168.657 > F table 3.12, so service quality has a positive influence on the decision. purchase. The results of the multiple linear regression test which has the equation Y = 2.211 + 0.529 Xı + 0.410 The results of the coefficient of determination test show that the value (R Square) obtained is 0.814 (81.4%) indicating that product quality and service quality have an influence on purchasing decisions by 81.4%.